2018
DOI: 10.1016/j.vetimm.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Low pathogenic avian influenza virus infection increases the staining intensity of KUL01+ cells including macrophages yet decrease of the staining intensity of KUL01+ cells using clodronate liposomes did not affect the viral genome loads in chickens

Abstract: The effect of depletion of macrophages using clodronate liposomes as well as macrophage response following viral infections have been studied in various mouse-virus infection models, but they have not been extensively studied in chickens relevant to virus infections. When we infected day 6 chickens with H4N6 low pathogenic avian influenza virus (LPAIV), we observed that H4N6 LPAIV infection increased the staining intensity of KUL01+ cells in trachea, lungs and duodenum of chickens at 3 days post-infection. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
3
3
0
Order By: Relevance
“…Furthermore, an increase in the percentages of CD3 + TCRγδ + lymphocytes in the ileum of chickens inoculated with 20Ch557/H6N2 virus was observed ( Figure 3B , p < 0.05), being in part due to an increase in CD3 + TCRγδ + CD8a + subpopulation. Besides, the macrophage population positive for staining of KUL01 marker showed a trend to increase in proportion in lamina propria from ileum from 20Ch557/H6N2 chickens ( Figure 3C ), as described during LPAIV infection ( Abdul-Cader et al, 2018 ). The percentages of other subsets analyzed from ileum did not show differences between groups (data not shown).…”
Section: Resultssupporting
confidence: 68%
“…Furthermore, an increase in the percentages of CD3 + TCRγδ + lymphocytes in the ileum of chickens inoculated with 20Ch557/H6N2 virus was observed ( Figure 3B , p < 0.05), being in part due to an increase in CD3 + TCRγδ + CD8a + subpopulation. Besides, the macrophage population positive for staining of KUL01 marker showed a trend to increase in proportion in lamina propria from ileum from 20Ch557/H6N2 chickens ( Figure 3C ), as described during LPAIV infection ( Abdul-Cader et al, 2018 ). The percentages of other subsets analyzed from ileum did not show differences between groups (data not shown).…”
Section: Resultssupporting
confidence: 68%
“…Furthermore, an increase in the percentages of CD3+TCRγδ+ lymphocytes in the ileum of chickens inoculated with 20Ch557/H6N2 virus was observed (Fig 3B, p < 0.05), being in part due to an increase in CD3+TCRγδ+ CD8a+ subpopulation. Besides, macrophage population positive for staining of KUL01 marker showed a trend to increase in proportion in lamina propria from ileum from 20Ch557/H6N2 chickens (Fig 3C ), as described during LPAIV infection 13 . The percentages of other subsets analyzed from ileum did not show differences between groups (data not shown).…”
Section: Virus/groupsupporting
confidence: 73%
“…Our immunophenotyping analysis also found two distinct populations of KUL-01+ cells, of which both KUL-01 hi and KUL-01 Lo populations were found to be significantly higher in the CpG-ODN (10 μg) adjuvant vaccinated chickens. A previous study also noted a similar distinction in the KUL-01+ cell population while investigating anti-AIV responses [ 43 ], and furthermore, another study indicated that KUL-01 hi cells possess enhanced phagocytic and tissue migratory activity in chickens [ 44 ]. However, it remains to be investigated if these two phenotypically distinct populations of macrophages induced in response to CpG-ODN stimulation have any biologically distinct functions in chickens.…”
Section: Discussionmentioning
confidence: 73%